(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
The perception of aesthetics varies from person to person and is influenced by personal experiences and social environment. Classical cultures of Greece and Rome based their standards of beauty on set rules of proportion and composition.